2018
DOI: 10.1108/ijem-12-2016-0268
|View full text |Cite
|
Sign up to set email alerts
|

Online search for information about universities: a Hong Kong study

Abstract: PurposeA fuller understanding of the information search behaviour of prospective students in the digital era is one of the keys to success in university recruitment. The purpose of this paper is to investigate students’ university choice factors in relation to the online environment.Design/methodology/approachIn total, 637 samples from 11 private higher education institutions were collected and tested against assumptions before performing statistical analysis including exploratory factor analysis and mean comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 48 publications
3
17
0
Order By: Relevance
“…It leads to greater "consumerist behavior" as prospective students seek "value for money" and it becomes a major part of their decision making. Other factors include declining university-age population (Wong et al, 2018), changing student loan schemes (Soutar and Turner, 2002) and shifting the supply of higher education that exceeds the demand (Brown et al, 2009). It is therefore crucial for HEIs to have a good understanding of the choice and decisionmaking process of their prospective students to have the edge over the other competitors in the recruitment market (Maringe, 2006;Brown et al, 2009).…”
Section: Critical Literature Review Marketing In Higher Educationmentioning
confidence: 99%
“…It leads to greater "consumerist behavior" as prospective students seek "value for money" and it becomes a major part of their decision making. Other factors include declining university-age population (Wong et al, 2018), changing student loan schemes (Soutar and Turner, 2002) and shifting the supply of higher education that exceeds the demand (Brown et al, 2009). It is therefore crucial for HEIs to have a good understanding of the choice and decisionmaking process of their prospective students to have the edge over the other competitors in the recruitment market (Maringe, 2006;Brown et al, 2009).…”
Section: Critical Literature Review Marketing In Higher Educationmentioning
confidence: 99%
“…This research aims to contribute to both university information search and student attitude literature. First, while previous research has addressed factors affecting students in making their university choice (Wong et al , 2018; Ming, 2010; Simões and Soares, 2010), this study used TPB to examine the key factors influencing students’ behavior when seeking advice from others about university choice. Second, the study expands the single information source effect on the combined effect by using high susceptibility to online information and low susceptibility to online information.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the relevant research regarding university choice lacks theoretical frameworks for explaining its reasons and impacts (Wong et al , 2018; Briggs, and Wilson, 2007; Hemsley-Brown, 2012; Maringe, 2006). For example, Maringe (2006) replicated the principal data instrument from James et al (1999) and Price et al (2003) to identify factors influencing university choice without applying theoretical frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Bonnema and Van der Waldt (2008) identified key needs as information related to employment, course content, student experience, sports, and finance. Wong et al (2018) examined the types of information students search for online on the higher education decision-making process. The authors reported four constructs that are perceived as important by students in their online search behavior: university reputation, eligibility and affordability, teaching and learning, and university tangibility.…”
Section: Students' Irs and Sourcesmentioning
confidence: 99%